2021
DOI: 10.1177/20597002211020881
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality in the chronic stage of concussion is associated with poorer recovery: A systematic review

Abstract: Background Recovery from a concussion varies based on a multitude of factors. One such factor is sleep disturbances. In our prior review, it was observed that in the acute phase, sleep disturbances are predictive of poor outcomes following a concussion. The literature gap remains on how sleep in the chronic phase of recovery affects outcomes. Objective To examine the association between sleep quality during the chronic stage of concussion and post-concussion outcomes. Literature Survey: Literature searches wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…Sleep dysregulation is a risk factor for prolonged recovery. One recent systematic review found that poor sleep was predictive of poor long-term outcomes in the acute phase of concussion recovery [ 6 ], while another systematic review found that poor sleep in the chronic phase of recovery was associated with poor cognitive functioning (executive function and working memory) and emotional regulation [ 7 ]. Currently, it is unknown if treatment for sleep disturbances in individuals with a concussion could impact recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep dysregulation is a risk factor for prolonged recovery. One recent systematic review found that poor sleep was predictive of poor long-term outcomes in the acute phase of concussion recovery [ 6 ], while another systematic review found that poor sleep in the chronic phase of recovery was associated with poor cognitive functioning (executive function and working memory) and emotional regulation [ 7 ]. Currently, it is unknown if treatment for sleep disturbances in individuals with a concussion could impact recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Poor sleep in the acute phase of a concussion is associated with prolonged recovery including more postconcussion symptoms with higher severity 4. Poor sleep in the chronic phase of concussion is associated with decreased cognitive functioning (executive function and working memory) and decreased emotional regulation 5…”
mentioning
confidence: 99%
“…Poor sleep is associated with prolonged recovery following concussion,4,5 and insomnia is the most commonly reported sleep disturbance in the concussion population 3. CBT-I may assist in the recovery process by improving sleep and potentially improving postconcussion symptoms.…”
mentioning
confidence: 99%
See 1 more Smart Citation